Iodine deficiency disorders and their elimination - Pearce, Elizabeth N. (Springer, 2017)
Iodine is an essential micronutrient and an integral component of the thyroid hormones, which are required for normal growth and development. The iodine deficiency disorders (IDD) encompass a spectrum of adverse health effects including goiter, cretinism, hypothyroidism, growth retardation, and increased pregnancy loss and infant mortality. This volume summarizes the current understanding of the effects of iodine deficiency as well as iodine excess. It also discusses best practices for salt iodization, the mainstay of global IDD prevention efforts, and other forms of food fortification. The effectiveness of iodine supplementation for vulnerable populations, an evolving strategy in many regions, is also described. Low level environmental exposure to chemicals such as perchlorate and thiocyanate, which competitively block thyroidal iodine uptake, appears to be ubiquitous worldwide. There has been recent concern that such environmental exposures might pose a health hazard by inducing or aggravating underlying thyroid dysfunction. This up-to-date volume explores both the effects of iodine deficiency as well as the best strategies for IDD prevention.
Includes index.
Keywords: Iodine deficiency diseases.; elektronické knihy; electronic books